An empirical evaluation of the User Engagement Scale (UES) in online news environments. Issue 4 (July 2015) - O'Brien, Heather; Cairns, Paul
Highlights We examined the robustness of the User Engagement Scale (UES). Three studies were conducted in Canada and the United Kingdom. The UES sub-scales were reliable across three samples of online news browser. A four-factor structure, rather than six, may be more appropriate. The UES differentiated between online news sources and experimental conditions.